Emergency neck MRI: feasibility and diagnostic accuracy in cases of neck infection - Nurminen J; Velhonoja J; Heikkinen J; Happonen T; Nyman M; Irjala H; Soukka T; Mattila K; Hirvonen J (SAGE PUBLICATIONS LTD, 2022)
Background: Computed tomography (CT) has traditionally been the first-line imaging method in neck emergencies such as deep neck infections. Due to superior soft-tissue contrast, magnetic resonance imaging (MRI) may be an alternative to CT, also in emergency situations.
Purpose: To characterize the use of routine MRI in neck emergencies, with an emphasis on clinical feasibility and diagnostic accuracy in cases of neck infection.
Material and Methods: We conducted a retrospective cohort study of all primary neck MRI scans performed using a 3-T MRI device during a five-year follow-up period in a tertiary emergency radiology department. Imaging data were compared with final clinical diagnosis and surgical findings as reference standards.
Results: The search identified 461 primary neck MRI scans, of which 334 (72%) were performed on the basis of clinical suspicion of infection. Radiological evidence of infection was observed in 95% of these scans, and at least one abscess was detected in 229 cases (72% of confirmed infection). MRI had an overall technical success rate of 95% and had high positive predictive value for both infection (0.98) and detection of abscess (0.95).
Conclusion: We found that emergency neck MRI can be successfully performed on most patients, and that MRI detects neck infection with a high accuracy. These results suggest that MRI may be an alternative to CT as the first or only imaging modality in neck emergencies.